Zebrafish, a Model to Develop Nanotherapeutics That Control Neutrophils Response During Inflammation - Vilos-Ortiz, C (Elsevier B.V., 2019)
Neutrophils are crucial modulators of the inflammation process, and their uncontrolled response worsens several chronic pathologies. The p38 mitogen-activated protein kinases (MAPKs) activity is critical for normal immune and inflammatory response through the regulation of pro-inflammatory cytokines synthesis. In this work, we study the effect of hybrid lipid–polymer nanoparticles loaded with the p38 MAPK inhibitor SB203580 in an acute and chronic inflammatory model in zebrafish containing a transgenic neutrophil cell line that constitutively expresses a green fluorescent protein. We identify the existence of at least two neutrophils subpopulation involved in the response during the acute inflammation triggered; a first-responder p38α–independent subset and a second-responder p38α-dependent subset. In the case of chronic inflammation, neutrophils recruited in the intestine only during the inflammation process, migrate in a p38α-dependent manner. Likewise, we establish that SB203580–loaded in NPs exerts their action during at least a double period than the inhibitor administers directly in both types of inflammation. Our results demonstrate the exceptional potential of the zebrafish as an inflammatory model for studying novel nanotherapeutics that selectively inhibit the neutrophils response, and to identify functional neutrophils subpopulations involved in the inflammation process. © 2019 Elsevier B.V.
Keywords: Zebrafish; Acute & chronic inflammation; Neutrophil recruitment; p38 MAP Kinase; Polymeric nanoparticles